Математические модели процессов вспенивания вторичного полиэтилена - Бухкало, Светлана Ивановна; Иглин, Сергей Петрович; Ольховская, Оксана Игоревна (Российский государственный университет им. А. Н. Косыгина, 2017)
Рассмотрены некоторые особенности повышения эффективности использования ТБО на комплексном предприятии, которое может обеспечивать все свои энергетические потребности самостоятельно. Исследования направлены на изучение таких вопросов, как разработка моделей утилизации-модификации полимерной части ТБО. При этом учитывались факторы выбора научно-обоснованных методов переработки и утилизации полимеров; разработка необходимых технологических схем и оборудования для переработки полимерных отходов; выбор предприятий для реализации утилизации полимеров и вида энергетических ресурсов для реализации этих проектных решений.

Some features of the possibilities of solving evidence-based problems of improving the use of wastes of different industries on a complex enterprise that can provide all its energy needs alone. The problem of wastes utilization and recycling is present as complex research and analysis of energy- and resource saving processes for treatment of polymer wastes of various origin. The research focused on the study of issues such as the development of models of waste-modifying polymer. The investigation are focused in researching such problems as selection of scientific based methods of wastes to be utilized or recycled; the development of appropriated process flow sheets and choice of modifications additives and equipment for polymers waste recycling. The choice of appropriate plants with selected energy resources is very important for projects realization.
Mathematical model for foaming recycled polyethylene
Keywords: интегрированные энергосберегающие технологии; интегрированные ресурсосберегающие технологии; объект научно-обоснованной технологии; модели вспенивания; integrated energy technologies; evidence-based methods; wastes conversion and recycling